(untitled) (Third Sector Social Economic Review, 2022)
This study aims to investigate both the momentum and contrarian anomalies (strategies) that may exist in the cryptocurrency market, focusing especially on Bitcoin. Daily Bitcoin prices were taken from a period starting 02.02.2012 and ending 27.02.2020 and used in the wild bootstrap automatic variance ratio (WBAVR) test proposed by Kim (2009). This test is robust to non-normality and conditional heteroscedasticity which are the main characteristics of financial time series, therefore, making it a valid test to be used to measure the momentum and contrarian effects. Results of the study demonstrate that: (1) There are both momentum and contrarian anomalies in Bitcoin price movements; (2) Bitcoin prices are generally predicted with the past price movements; (3) Abnormal returns are more likely to be obtained by employing contrarian strategy compared to momentum strategy. This study gives important information about the Bitcoin price movements to savings owners, portfolio managers and institutional investors who follow an investment strategy with past price movements.